Tippins and Wittman Revisited: Law, Social Science, and the Role of the Child Custody Expert 14 Years Later. (20th January 2019) - Amundson, Jon; Lux, Glenda
Abstract : It has been 14 years since Tippins and Wittmann (2005 ) voiced concern for the overreaching role the expert may play in matters of family law. This article sets their levels of inference within the context of the culture of both law and social science. We examine how inferences are impacted by the relative emphasis child custody experts give to the five stakeholders involved in child custody evaluations (CCEs): courts, lawyers, parents, children, and professional governing bodies. Acculturation of the assessor to law contributes to more egregious inferences, versus the more modest ones Tippins and Wittmann advocated. How evaluators prioritize stakeholders shapes their opinion and methodology. We offer an expanded perspective that views how their levels of inference are manifest in reports, methodology, and recommendations and the influence of the culture of law and the mindset of the clinician. We hope to encourage clinicians to find ways to operationalize clinical humility, assume their proper role, and remain true to their master identity as licensed mental health professionals and their proper sphere of authority. Key Points for the Family Court Community: Tippins and Wittmann's (2005 ) levels of inference should be understood within the context of both law and social science. Tippins and Wittmann's (2005 ) lower levels of influence are most likely seen in child custody evaluations (CCE's) with a biopsychosocial emphasis. Biopsychosocial proficiency is the specialized skill and knowledge that supports expert CCE opinions and which best serves mental health disciplines. There are 5 stakeholders involved in CCEs: courts, lawyers, parents, children, and professional governing bodies. Inference levels are influenced by the culture of law and the mindset of the clinician relative to the attention given to the stakeholders. Child custody evaluators need to understand how their methodologies and recommendations are influenced by their mindset and orientation toward the stakeholders, the culture of law, and the culture of social science. By understanding the two types of authority: authority by role and authority by status, mental health professionals can remain true to their professional identity and to their proper sphere of authority within their role as child custody experts. The more a CCE becomes acculturated toward law, the more Tippins and Wittmann's seminal concern for ethics and scope of practice emerges.